Developments in environmental education in New Zealand - Claire Freeman; David Chapman (Environmental Association of Southern Africa, 1999)
New Zealand has experienced a recent resurgence of interest in environmental education, particularly in the informal sector. Whilst this resurgence is welcomed it takes place against a background of earlier frustrated initiatives and within a socio- political context where the emphasis is on market economics and constrained resources. This paper assesses both the successes and failures of environmental education in recent years, before focusing on current developments in environmental education in both the informal and formal sectors. Finally the paper explores the potential for real progress in environmental education in New Zealand against this background of economic and environmental competition.